SAT0176 THERAPEUTIC APHERESIS DURING PREGNANCY IN RHEUMATIC DISEASES. (13th June 2020) - Colpo, A.; Marson, P.; Tison, T.; Zambon, A.; La Rosa, A.; Zanetti, E.; Ruffatti, A.; De Silvestro, G.; Hoxha, A.
Abstract : Background: Therapeutic apheresis (TA) represents a therapeutic option in pre-existing conditions or rheumatic diseases that occur during gestation. Although pregnancy is not a contraindication itself, due to the lack of evidence-based guidelines and the alleged risk of maternal and/or fetal adverse events, there is general resistance to its application during pregnancy. Objectives: In this observational study we aimed to evaluate the efficacy and safety of TA in high-risk pregnancies in patients with rheumatic diseases, followed over a decade in a tertiary Center. Methods: Between January 2005 and April 2019, 843 TA procedures were performed during 51 pregnancies in 43 patients: 745 plasma exchange sessions and 98 immunoabsorption sessions. TA was performed in 29 (57%) pregnancies of 21 (48.8%) patients with antiphospholipid antibody syndrome (APS), in 20 (39.2%) pregnancies of 20 (46.5%) patients with congenital heart block (CHB), in 1 (1.9%) pregnancy of 1 (2.3%) patient with systemic sclerosis (SSc) and 1 (1.9%) pregnancy of 1 (2.3%) patient affected by lupic nephritis (SLE). Results: During the period considered, apheresis sessions applied to pregnant women were 7.1% of the total (n = 13.251). The average age at the first treatment was 33 years (range 24-43). The mean management age at the first apheretic treatment was 21 weeks (range 4-32). Twelve (1.4%) apheresis sessions were complicated by adverse events, none required or prolonged hospitalization. There were 44 (86.3%) live births, 3 (5.9%) spontaneous abortions and 2 (3.9%) voluntary terminations of pregnancy, 2 (3.9%) lost to follow-up. The average gestational age at birth was 35 weeks (range 24-37) and cesarean section was performed in 41 (80.4%) cases. TA was added to conventional therapy in 24/29 (82.7%) patients with APS, to the detection of fetal cardiac activity, while in 5/26 (17.3%) it was introduced when the first signs of pregnancy complications such as mild preclampsia, HELLP and IUGR were detected. TA was started within 24 hours of atrioventricular block (AVB) detection; 10/20 (50%) mothers with CHB were diagnosed with 2nd degree AVB, 9/20 (45%) with 3rd degree AVB and one (5%) with sinus bradycardia and endocardial fibroelastosis. The patient with SSc was treated with TA twice a week from the 32nd SG until delivery, which occurred at the 36th SG, due to severe IUGR and oligohydramnios. The patient with SLE complicated by lupic nephritis was treated with TA twice a week, from the 26th SG until the birth, which took place at the 31st SG. Conclusion: Our data have shown that TA in pregnancy is well tolerated. Close collaboration between rheumatologist, obstetrician and specialist in TA is essential to ensure a successful outcome of high-risk pregnancies. Disclosure of Interests: Anna Colpo: None declared, Piero Marson: None declared, Tiziana Tison: None declared, Alessandra Zambon: None declared, Annalisa La Rosa: None declared, Ermella Zanetti: None declared, Amelia Ruffatti: None declared, Giustina De Silvestro: None declared, Ariela Hoxha Speakers bureau: Celgene, UCB, Novartis, Sanofi, Werfen